SEMIOTICS, RHETORICAL LANGUAGE, AND FIGURATIVE LANGUAGE OF W.S RENDRA’S POETRY - M. Arifin Zaidin; Patmawati Halim (Prosiding Seminar Nasional dan Internasional HISKI, 2023)
Semiotic analysis of the poems "The Prayer" and "God, I Love You" is critical for comprehending the meaning of poetry by revealing and imparting meaning to the poems' contents. Poetry is a meaningful structure because it is a sign system that utilizes language as a communication medium. Language has become a semiotic system in literary works of poetry, with meanings distinct from sound, music, art, and color. Language encodes and organizes semantic relationships such that the meaning of words can be learned by observing their use in standard texts. The present study was conducted to illuminate linguistic semiotics in W.S Rendra's poems "The Prayer" and "God, I Love You" and go deeper into the usage of literary semiotics in the two poems. This study belongs to a literature review using a qualitative approach, emphasizing natural facts in connection to the context of their existence. The poetry text, linguistics, flowery language, and figurative language in the poems "The Prayer" and "God, I Love You" served as variables in this study. Without conducting interviews, surveys, or observations, we undertook a discovery study of the semiotics of language and the literary conventions of WS Rendra's poetry "The Prayer" and "God, I Love You." The primary and secondary data of this study were compiled using documentation techniques. The results indicated that WS Rendra's poems "The Prayer" and "God, I Love You" use words, phrases, clauses, and sentences. In addition, the poet employs rhetorical devices such as repetition, reticence, parallelism, assonance, sentence condensation, paradoxes, and figurative devices such as metaphor and hyperbole, in "God, I Love You." Meanwhile, "The Prayer" contains a variety of rhetorical devices, including repetition, tautology, parallelism, assonance, enumeration, condensation, and figurative language, namely litotes, hyperbole, allegory, and personification.